2006
DOI: 10.1249/01.mss.0000227314.85728.35
|View full text |Cite
|
Sign up to set email alerts
|

Androgenic Responses to Resistance Exercise

Abstract: In summary, these data demonstrated that: 1) feeding after RE increased AR content, which may result in increased testosterone uptake, and thus enhanced luteinizing hormone secretion via feedback mechanisms; and 2) LCLT supplementation upregulated AR content, which may promote recovery from RE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
42
3
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(51 citation statements)
references
References 30 publications
4
42
3
1
Order By: Relevance
“…Some of them work, some of them is just a waste of money. Nonetheless, well established creatine monohydrate, BCAAs, L-glutamine, L-carnitine, L-arginine-α-ketoglutarate and weight training combined with of course protein whey enhance muscle hypertrophy and force production [8,25,4]. тренування, яке призводить до гіпертрофії і проліферації скелетних м'язових волокон.…”
Section: Discussionmentioning
confidence: 99%
“…Some of them work, some of them is just a waste of money. Nonetheless, well established creatine monohydrate, BCAAs, L-glutamine, L-carnitine, L-arginine-α-ketoglutarate and weight training combined with of course protein whey enhance muscle hypertrophy and force production [8,25,4]. тренування, яке призводить до гіпертрофії і проліферації скелетних м'язових волокон.…”
Section: Discussionmentioning
confidence: 99%
“…To test this hypothesis, we recently examined the effects of feeding on the post-resistance exercise androgen receptor response [61] . We surmised that the decrease in testosterone concentrations following post-exercise feeding would be associated with an increase in androgen receptor content.…”
Section: Testosteronementioning
confidence: 99%
“…Supplemental protein intake facilitates MPS during resistance training and induces a positive net protein balance [1], this is a positive algebraic event when protein synthesis is greater than protein breakdown [2,3]. During resistance exercise, athletes are generally required to consume more protein for restoration and reformation of damaged muscle [4].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that a high protein intake (1.6-1.8 g/kg/day) improves body composition, enhances lean body mass [5], and affects anabolic hormones that are related to muscle remodelling [6]. Previous studies have reported that resistance exercise stimulates the secretion of anabolic growth hormone and testosterone [4], which stimulates MPS [7]. During resistance exercise, a high protein intake reportedly increases resting testosterone, cortisol, growth hormone, and insulin levels [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation